EVOLUTION IN RESISTANCE AGAINST TETRACYCLINE IN BACTERIA - Muhammad Ehetisham ul Haq; Muhammad Usman; Usama Ahmad; Muhammad Kamran; Huma Abbas; Muhammad Umar Shahbaz; Waseem Abbas; Qamar Anser Tufail Khan; Salman Ahmad (Journal of Animal and Plant Sciences, 2026)
Tetracyclines used to be potent broad-spectrum antibiotics, but the rampant use of these drugs in the clinic and agriculture has led to widespread resistance among bacterial populations. This review outlines the evolutionary foundation of tetracycline resistance by emphasizing the primary molecular mechanisms that comprise efflux pumps, ribosomal protection proteins, and enzymatic inactivation. Efflux systems, programmed by heterogeneous tet genes, are prevalent in Gram-negative bacteria, while ribosomal protection proteins occur more frequently in Gram-positive strains. Enzymatic inactivation, although less frequent, is gaining notoriety due to the increase in Tet(X) variants. The review also addresses the involvement of horizontal gene transfer via plasmids, transposons, and integrative elements in spreading resistance between clinical, veterinary, and environmental environments. Ecological surveys show that soil, water, animal, and plant-associated microbiomes are primary reservoirs of tet genes, which guarantee their persistence even without direct antibiotic pressure. Evolutionary analyses show that Gram-negative bacteria evolve faster than Gram-positives, highlighting their supremacy in resistance propagation. Together, this review presents an integrated overview of the genetic, ecological, and evolutionary forces of tetracycline resistance and highlights the worldwide health consequences of its endurance.
Keywords: Tetracycline; efflux pumps; ribosomal protection; enzymatic inactivation; horizontal gene transfer; resistance evolution; ecology